(untitled) (Research, Society and Development, 2022)
The present study aims to analyze the epidemiological profile, diagnosis and treatment of hemophiliac patients who developed inhibitors and who are treated by the Hemotherapy Center of Sergipe (HEMOSE). The research consists of a retrospective analysis based on information contained in the medical records of patients with hemophilia A who were treated in the outpatient sector of HEMOSE during the period from January 2010 to January 2018. For this purpose, variables such as gender were evaluated , age, location, color, severity, symptoms, inhibitor titer, and treatment. Of the patients evaluated, 17 (18%) had inhibitors, and, of this total, 11 (64.7%) were brown. In addition, most patients were diagnosed with hemophilia A and detected the presence of inhibitor in the age group between 0 and 10 years. Regarding the severity of the disease, 11 (64.7%) had the severe form. With regard to treatment before the development of inhibitors, the majority, 10 (59%), used an association of Factor VIII with Factor VIIIr. It is also noteworthy that the majority of patients developed low titer antibodies, with a rate of 82% (14). It is also considered that the results found in this study are in accordance with what is found in the literature on the subject and that the information obtained provides a better understanding of the profile of patients with hemophilia A who have inhibitors, which can then improve care. of these patients.